Religious and Moral Values Learning Strategies in Early Childhood from an Islamic Perspective - Ismail - (PG-PAUD Trunojoyo, 2026)
Religious and moral values (RMV) education in early childhood is a fundamental component in shaping Islamic character and holistic child development. This study aims to analyze the objectives, curriculum, methods, media, and evaluation of RMV learning from an Islamic perspective. The research employed a qualitative library research method, involving systematic collection, classification, and analysis of classical Islamic texts, national curriculum documents, and international journal articles. Data were collected from indexed databases (Scopus, DOAJ, Google Scholar) using keywords related to Islamic early childhood education and moral development, while analysis was conducted through content analysis focusing on thematic categorization and interpretation. Sources examined originate from various educational contexts, including Indonesian early childhood education settings and broader international perspectives. The results of the study show that RMV learning emphasizes the internalization of monotheism, worship practices, noble character, and social responsibility. Curriculum implementation requires integration between national PAUD standards and Islamic values, while effective learning methods include habituation, role modeling, storytelling, dialogical interaction, and play-based approaches. Appropriate media include visual, audio, audiovisual, and digital tools designed to suit the developmental stage of early childhood. Evaluation prioritizes observation of children's daily attitudes and behaviors, supported by portfolios and home–school collaboration. The findings provide practical implications for educators and PAUD institutions.